1991
DOI: 10.1093/ajcn/53.6.1466
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid requirements for smokers: analysis of a population survey

Abstract: The recommended dietary allowance (RDA) of ascorbic acid for smokers was recently increased from 60 to 100 mg. To determine whether this new RDA for smokers is sufficient to reduce the risk of low serum ascorbic acid (AA) concentrations (LoC) to the same concentration as nonsmokers, we analyzed the dietary intakes and serum concentrations of AA in 11,582 adult respondents in the National Health and Nutrition Examination Survey (1976-1980). Serum AA concentrations and the risk of LoC (serum ascorbic acid levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 21 publications
1
41
1
3
Order By: Relevance
“…This is in line with previous studies demonstrating that long-term exposure to SHS decreases plasma ascorbic acid in both active and passive smokers. 7,12 Furthermore, in vitro data exposing human plasma to CS suggest that ascorbic acid is the first antioxidant to be consumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous studies demonstrating that long-term exposure to SHS decreases plasma ascorbic acid in both active and passive smokers. 7,12 Furthermore, in vitro data exposing human plasma to CS suggest that ascorbic acid is the first antioxidant to be consumed.…”
Section: Discussionmentioning
confidence: 99%
“…11 Therefore, this could be one factor leading to the high incidence of CHD in smokers, who also have decreased plasma levels of certain antioxidants. 12 However, only fractional and, to some extent, controversial evidence concerning the connection between CS and lipid peroxidation has been reported so far from studies conducted with active smokers or under in vitro conditions. [13][14][15] To understand the pathogenesis underlining the connection between CHD and passive smoking, we assessed the acute effect of passive smoking on LDL metabolism.…”
mentioning
confidence: 99%
“…The inverse relationship between smoking and plasma vitamin C levels is well reported, even for passive smoking. 20 Schectman et al 21 suggested that smokers need more vitamin C to reach the same plasma levels as non-smokers. Vegetables and fruits serve as primary contributors to total vitamin C intake, 22 whereas dietary supplements of vitamin C and other antioxidants have failed to demonstrate consistent therapeutic benefits, 23 therefore grapefruit was choosen to influence vitamin C status.…”
Section: Plasma Vitamin C Levelsmentioning
confidence: 99%
“…These results demonstrate the protective effect of dietary ascorbate against oxidative damage to human sperm DNA. This protective effect may be especially relevant to about one third of the male population who have low ascorbate levels because of poor diets or smoking (139,143,144). Their progeny may be at a higher risk for birth defects and childhood cancer.…”
Section: Progression and Clonal Instabilitymentioning
confidence: 99%